Impact of Free Contributions on Private Benefits in Online Healthcare Communities. Issue 4 (2nd October 2019) - Zhang, Min; Guo, Xitong; Wu, Tianshi
ABSTRACT: Online healthcare communities (OHCs) have become increasingly popular and now impact the way that doctors connect with patients. In the OHCs, many doctors have become multitype service providers. Considering that doctors' contributions to online free services and the private benefits of online paid services are both important, it is vital for platforms to encourage doctors' online participation. Yet little is known about the spillover effects of the contributions to online free services on doctors' private benefits regarding paid services. In our study, we investigate the relationship between online free services and the private benefits of online paid services based on the theory of the spillover effects and the signaling theory. We analyze a panel data set from 1, 349 doctors participating in an OHCs in China. Our results indicate that participation in online free services significantly increases the private benefits of family doctors before a certain value. Moreover, a doctor's ranking has a moderating effect on this relationship. Our results highlight the spillover effects of an online free service and make contributions to signaling theory, and they have important implications for doctors, OHCs platform, and governments.